Comparative functional outcome of supracondylar femoral fracture stabilized with cross and end threaded intramedullary pinning in dogs - GILL, KIRANDEEP KAUR; KUMAR, ASHWANI; SANGWAN, VANDANA; ANAND, ARUN; MAHAJAN, SHASHI KANT; MOHINDROO, JITENDER (The Indian Journal of Animal Sciences, 2018)
The study was conducted on 24 clinical cases of dogs (with 26 fractures) suffering from supracondylar fractures of femur which were stabilized using cancellous negative intramedullary (IM) end-threaded pin with 5 screws (Group I, n=8), cross-pinning (Group II, n=8, 9 fractures) and cancellous negative end threaded IM pin having 10– 18 threads (Group III, n=8, 9 fractures). Data collected included signalment, fracture characteristics (etiology, duration, Salter-Harris classification, pre-operative and post-operative displacement), surgical information (implant size, surgical duration) and outcome assessment (functional outcome and complications). Cross pinning technique used to stabilize supracondylar fracture of femur adversely affects flexion angles of stifle joint leading to joint stiffness compared to either of the end threaded pinning techniques; however, extension angles remain unaffected. Early weight bearing in group II suggested that crossing pinning is a rigid fixation technique compared to either end threaded pinning techniques. Minor implant related complications were recorded in group II (3) followed by group 3 (2) and group 1(1) which were managed successfully. Though fixation of supracondylar fractures using double armed end threaded pin with 5 cancellous negative threads was associated with shorter duration of surgery, and fewer postoperative complications; however, based on formation of minimal and smooth callus and better functional outcome, conventional end threaded pin with 10–18 cancellous negative threads was assessed to be a better fixation technique and was recommended for the repair of supracondylar fractures of femur in dogs.